Physiological capacity and training routines of elite cross-country skiers: Approaching the upper limits of human endurance - Sandbakk, O.; Holmberg, H. C. (International Journal of Sports Physiology and Performance, 2017)
Cross-country (XC) skiing is one of the most demanding of endurance sports, involving protracted competitions on varying terrain employing a variety of skiing techniques that require upper- and/or lower-body work to different extents. Through more effective training and extensive improvements in equipment and track preparation, the speed of cross-country ski races has increased more than that of any other winter Olympic sport, and, in addition, new types of racing events have been introduced. To a certain extent this has altered the optimal physiological capacity required to win, and the training routines of successful skiers have evolved accordingly. The long-standing tradition of researchers working closely with XC-ski coaches and athletes to monitor progress, improve training, and refine skiing techniques has provided unique physiological insights revealing how these athletes are approaching the upper limits of human endurance. This review summarizes current scientific knowledge concerning the demands involved in elite XC skiing, as well as the physiological capacity and training routines of the best athletes.